2011
DOI: 10.5603/fhc.2011.0037
|View full text |Cite
|
Sign up to set email alerts
|

JAK2 mutation status, hemostatic risk factors and thrombophilic factors in essential thrombocythemia (ET) patients

Abstract: The recently discovered JAK2 V617F point mutation, found in 50-60% of ET patients, has been reported to be associated with a higher risk of thrombotic events. In this study, we explored if JAK2 V617F mutation, or coexisting thrombophilic and hemostatic risk factors, contributed to these complications. We examined 32 patients with ET, and looked for pathogenetic JAK2 V617F mutation and prothrombotic genes mutations: factor V Leiden, prothrombin and MTHFR. We also evaluated plasma levels of fibrinogen, factors V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
3

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 17 publications
1
9
0
3
Order By: Relevance
“…Interestingly, this phenomenon existed not only in ET patients but also in all of patients with non-reactive elevated platelet count. Our results support the hypothesis that JAK2 V617F mutation activated TPOR pathway and led to hyperplasia of megakaryocytic progenitor cells [19].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, this phenomenon existed not only in ET patients but also in all of patients with non-reactive elevated platelet count. Our results support the hypothesis that JAK2 V617F mutation activated TPOR pathway and led to hyperplasia of megakaryocytic progenitor cells [19].…”
Section: Discussionsupporting
confidence: 90%
“…JAK2 V617F increases Bcl-xL expression in hematopoietic progenitor cells [17] and contributes to the development of erythrocytosis [18]. In addition, JAK2 V617F induces abnormal activation of thrombopoietin receptor (TPOR) and granulocyte colony-stimulating factor receptor (G-CSFR) pathway, leading to hyperplasia of megakaryocytic and granulocytic progenitor cells [19]. Because JAK2 V617F mutation promotes proliferation of multiple cell lineages, patients with such mutation exhibit increased numbers of mature and immature cells in peripheral blood.…”
Section: Introductionmentioning
confidence: 99%
“…Since large platelet represents new and immature platelet, particular studies indicated that JAK2 V617F mutation was significantly associated with increase of immature platelets [15,29]. It was supposed that JAK2 V617F may promote thrombopoiesis and caused to hyperplasia of megakaryocytic progenitor cells in the bone marrow [30].…”
Section: Discussionmentioning
confidence: 99%
“…3 Mutations in JAK2 are found in approximately 50-60% of cases of essential thrombocythaemia. 4 The clinical manifestations of essential thrombocythaemia result from platelet activation, 5 hyperviscosity, tissue hypoxia and vascular occlusion 6 with arterial thrombosis occurring more commonly than venous thrombosis. 7 Mesenteric and portal vein thrombosis are recognised rare complications of myeloproliferative disease.…”
Section: Discussionmentioning
confidence: 99%